2020
DOI: 10.1177/1538574420951315
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Neutrophil-Lymphocyte Ratio in Vascular Surgery: Systematic Review and Meta-Analysis

Abstract: Objective: The global burden of surgical vascular disease is increasing and with it, the need for cost-effective, accessible prognostic biomarkers to aid optimization of peri-operative outcomes. The neutrophil-lymphocyte ratio (NLR) is emerging as a potential candidate biomarker for perioperative risk stratification. We therefore performed this systematic review and meta-analysis on the prognostic value of elevated preoperative NLR in vascular surgery. Methods: We searched Embase (Ovid), Medline (Ovid), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…As the ratio of neutrophils to lymphocytes, NLR has also been found to be elevated in atherosclerosis (Balta et al 2016) and cardiovascular disease (Afari & Bhat 2016). More importantly, elevations in NLR have, in recent years, been also found to be of predictive value (both diagnostic and prognostic) in a range of cardiovascular (Kalay et al 2012;Borg Caruana et al 2020;Jackson et al 2020;Liu et al 2020) and ophthalmic conditions such as diabetic retinopathy and age-related macular degeneration (Ulu et al 2013;Ilhan et al 2015). The PLR is a similar emerging inflammatory biomarker that elevates in thrombocytosis and lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ratio of neutrophils to lymphocytes, NLR has also been found to be elevated in atherosclerosis (Balta et al 2016) and cardiovascular disease (Afari & Bhat 2016). More importantly, elevations in NLR have, in recent years, been also found to be of predictive value (both diagnostic and prognostic) in a range of cardiovascular (Kalay et al 2012;Borg Caruana et al 2020;Jackson et al 2020;Liu et al 2020) and ophthalmic conditions such as diabetic retinopathy and age-related macular degeneration (Ulu et al 2013;Ilhan et al 2015). The PLR is a similar emerging inflammatory biomarker that elevates in thrombocytosis and lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Jackson et al. 2020; Liu et al. 2020) and ophthalmic conditions such as diabetic retinopathy and age‐related macular degeneration (Ulu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between immune and non-immune agents are underlined including reperfusion injury, coronary endothelial dysfunction, and inflammation [ 66 ]. The meta-analysis performed by Jackson et al on patients referred for vascular procedures link the preoperative NLR to all-cause mortality and indicate the relation between immune and non-immune individual predisposition to over reactivity of the inflammatory system [ 67 ]. The results from our study, presenting increased postoperative NLR (above 3.5) as a significant mortality factor in multivariable analysis, is a compromise with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous published papers on oncological and vascular diseases, our experience has confirmed the role of the baseline NLR value as an excellent marker for inflammatory processes and a promising risk stratification tool [ 15 , 16 , 17 , 18 , 19 , 20 ]. Previous published studies evaluated the prognostic role of preoperative NLR values in vascular disease, and the importance of establishing a unique cut-off [ 20 , 21 ]. Kordzazdeh et al reported that a preoperative NLR > 5 could be considered as an independent predictor of 30-day mortality in patients treated for abdominal aortic aneurysms (AAA), irrespective of age, gender, comorbidities, AAA size, blood loss, and length of hospital stay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%